Design of under-tray for a formula SAE race car using CFD analysis (2018)
This project seeks to perform the preliminary design of an aerodynamic diffuser to be used in a three-dimensional model of a formula-type vehicle, using computational tools. For the development of this project, the state of the art was taken into account regarding Formula SAE racing vehicles, as well as the general literature on aerodynamics in racing vehicles. The development of the design involves three key moments: 1) The development of a theoretical framework, which defines the computational tools to be made and the physical models that these tools use. 2) Definition and optimization of the geometry in two dimensions that will compose the main structure of the diffuser. 3) Definition and optimization of the final geometry, in three dimensions, of the aerodynamic device. The parameters that were used for the optimization of the geometries, both in two and three dimensions, were the input angle and input area ratio.